Consideration of the contribution of operating a firefighting robot system for large fires to prevent COVID-19 infection among firefighters. (18th April 2023) - Fujita, Jun; Amano, Hisanori; Ohno, Kazunori; Tadokoro, Satoshi
Abstract : A firefighting robot system has been developed to replace firefighters in dangerous firefighting activities near the source of a large fire. Firefighting activities at the scene of a fire are tasks that require many people working in dense, coordinated cooperation, and there is concern about the spread of COVID-19 infection. This paper outlines the firefighting robot system developed by the authors and discusses its contribution to preventing COVID-19 infection when the robot system is applied to firefighting activities, taking into account the new normal. GRAPHICAL ABSTRACT: UF0001